2011
DOI: 10.1017/s0021932011000654
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Analysis of the Determinants of High-Risk Sexual Behaviour in Sub-Saharan Africa

Abstract: A number of authors have identified multiple concurrent sexual partnerships by both men and women to lie at the root of the HIV/AIDS epidemic in sub-Saharan Africa. This study applies multilevel models to Demographic and Health Survey data collected during 2003-2008 in 20 sub-Saharan African countries to examine the influence of social and cultural context on involvement with multiple sexual partnerships in the region, above and beyond the effects of individual characteristics. The findings provide support for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
57
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 35 publications
14
57
5
Order By: Relevance
“…The association between having multiple sex partners and being male are similar to findings from other studies [35]. Our findings indicated that club drug users 35 years or older were more likely to report having multiple sex partners in the past month than those younger than 25 years, regardless of marital status, which was contrary to the findings from previous studies in which younger people were more likely to have multiple sex partners [36,37]. The reason is unknown, but it is possible that compared to other populations, club drugs influence users’ sexual practices, or that middle-aged persons with multiple sex partners are more likely to report use of club drugs and were thus included in our study.…”
Section: Discussionsupporting
confidence: 68%
“…The association between having multiple sex partners and being male are similar to findings from other studies [35]. Our findings indicated that club drug users 35 years or older were more likely to report having multiple sex partners in the past month than those younger than 25 years, regardless of marital status, which was contrary to the findings from previous studies in which younger people were more likely to have multiple sex partners [36,37]. The reason is unknown, but it is possible that compared to other populations, club drugs influence users’ sexual practices, or that middle-aged persons with multiple sex partners are more likely to report use of club drugs and were thus included in our study.…”
Section: Discussionsupporting
confidence: 68%
“…DHS data for comparative (multilevel) analysis on how community characteristics affect specific outcomes has mainly been used in studies of health (Adekanmbi et al, 2013;Corsi et al, 2012;Uchudi, 2012;Uthman, 2010). By contrast, for education measures and especially for preschool attendance, evidence related to community is non-existent.…”
Section: Variablesmentioning
confidence: 99%
“…They described HIV as the outcome of societal, neighborhood, interpersonal, and individual level factors. When applied to substance use and sexual behaviors at a rural market, societal norms and national policies and laws provide a broad context in which opportunities for substance use and risky sex are made available for young people (Wagenaar, Tobler, & Komro, 2010;Xu & Chaloupka, 2011). The next level of influence is the neighborhood, which includes the market as an alcohol environment as well as the communities surrounding the market.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Introduction to alcohol at an early age may have lifelong consequences, while higher educational achievement may motivate people to think optimistically about the future and reduce the risk of substance use (Baker, Collins, & Leon, 2008;Edstrom & Khan, 2009;Uchidi, Magadi, & Mostazir, 2012). Understanding how factors at each of these levels influence young men's substance use and risky sexual behaviors may aid in the reduction of these risks.…”
Section: A N U S C R I P Tmentioning
confidence: 99%